Nutrition education with jigsaw method as an effort to prevent stunting in the Perak Timur Health Center area, Surabaya - Nur Hatijah; Taufiqurrahman Taufiqurrahman; Annas Buanasita (Community Empowerment, 2023)
East Java has a stunting toddler prevalence of 26.1% and Surabaya City has a stunting toddler prevalence of 17.44%. The purpose of this service activity is to empower the East Perak Community Health Center through nutrition education in the context of stunting prevention. Activities carried out in two stages of activity. The first activity is to provide training to become facilitators. The second activity provides assistance to partner cadres/communities as facilitators in counseling. The results of stunting prevention activities in the Tembok Dukuh Community Health Center in Surabaya City showed that the jigsaw method was more effective in improving the quality of toddler parenting than the lecture and demonstration methods (P<0.05). In addition, the results of this activity also showed a significant increase in knowledge. Cadres are also able to become facilitators in applying flashcards using the jigsaw method.